Analisis peran kepemimpinan dalam meningkatkan kinerja personil Ditlantas Polda Jabar masa periode 2023 - Nuramelia, Alya; Agustian Widya Yusuf, Ilham; Farihin, Ahmad (LP3M UNZAH GENGGONG, 2024)
In this era of globalization, the effectiveness of work in an organization is greatly influenced by the leadership in it. Leadership is not only an administrative function that ensures that tasks are carried out, but also an important element in inspiring, motivating, and guiding members of the organization towards achieving common goals. The purpose of this study is to analyze the role of leadership in improving the performance of members of the West Java Regional Police Traffic Directorate in the 2023 period. The method used in this study is Qualitative with a descriptive approach with interview data collection techniques, document studies and observations and data analysis used using data triangulation. The results of this study emphasize the importance of the role of leadership in improving the performance of members of the West Java Regional Police Traffic Directorate. The leadership applied is vertical, with leaders acting as role models and motivators who are able to direct and support their members in carrying out their duties. Strategies such as giving awards, empathy, and role models have proven effective in encouraging work productivity and disciplined behavior of members. These findings confirm that strong leadership contributes directly to the achievement of organizational goals, such as creating traffic safety and order.